The Palliative Role of Colchicine on Advanced Hilar Cholangiocarcinoma Patient with Socio-Economic Challenges: A Case Report - Yanto, Theo Audi; Mulia, Nathania Raphaeli; Kusuma, Yordan (Medicinus, 2025)
Cholangiocarcinoma is a rare, slow-growing tumor that commonly presents beyond the point of resectability. Current guidelines recommend chemotherapy and radiotherapy for inoperable cases. However, palliative resources are not always accessible for patients with socio-economic barriers. Meanwhile, colchicine is a cost-effective drug and possesses anticancer effects. Here, we present a 53-year-old man with a 6-month history of painless jaundice, severe pruritus, recurrent fever, progressively growing abdominal mass, loss of appetite, and significant weight loss. He was incapable to perform adequate self-care and remained bedridden. Courvoisier sign was noted. Liver function tests show hyperbilirubinemia with elevated CA 19-9 level. Abdominal MRI 3T and MRCP showed hilar cholangiocarcinoma and obliteration of the hepatic vein. The patient and his family did not have health insurance and lived on a minimum income. Considered inoperable, the patient received daily colchicine 1 mg. Within four months, his symptoms have subsided, and he could perform several house chores. Bilirubin also showed a decreasing trend. In neoplastic cells, colchicine inhibits cell mitosis by perturbing tubulin formation. Being widely available, colchicine can be a palliative drug for terminally ill patients with socio-economic challenges. Although it improves patient performance status, we recommend further studies and close monitoring for the use of colchicine in advanced cholangiocarcinoma cases.